Pengaruh Strategi Crossword Puzzle Terhadap Hasil Belajar Siswa Kelas V SD Negeri 08 Rambang Kuang: Crossword Puzzle, Hasil Belajar, IPS Kelas Tinggi - Amalisa, Yeni; Idris, Muhamad; Suryani, Ida (Indonesian Research Journal on Education, 2022)
Strategy Crossword Puzzle (crossword puzzle) is a strategy that can activate a learning atmosphere where in the game the player must fill in the empty spaces (in the form of white boxes)with letters that form a word based on the instructions given. Usually, the instructions are divided into "level" and "downhill" categories depending on the words that must be filled in. The purpose of this study was to determine whether there was an effect of the Crossword Puzzle Strategy on the learning outcomes of fifth-grade students at SD Negeri 08 Rambang Kuang. The method used in this research is a quantitative type of Quasi Experiment. The data collection techniques used are tests, observations, and documentation. The data obtained are then calculated using SPSS version 22. With the hypothesis testing criteria, namely t_count > t_(table) then H_a is accepted. The results obtained in this study are t_count = 4,521 > t_(table ) = 1.166980 It means that H_a is accepted. So it can be concluded that there is an effect of the Crossword Puzzle Strategy on the learning outcomes of the fifth-grade students of SD Negeri 08 Rambang Kuang.